Alcohol and tobacco use in individuals with type 2 diabetes: Study before and during the Covid-19 pandemic - Lins, Emilly Nascimento Pessoa; da Costa, Isabela Catarina Leão; Santos, Alessandro Henrique da Silva; Carvalho, Queliane Gomes da Silva; Cavalcanti, Belvania Ramos Ventura da Silva; Borba, Anna Karla de Oliveira Tito (Seven Editora, 2024)
Objective: To evaluate alcohol and tobacco use in individuals with type 2 diabetes mellitus before and during the COVID-19 pandemic. Method: A longitudinal study with a quantitative approach was carried out with 72 individuals with diabetes who were treated at the outpatient clinic of a public hospital in the city of Recife, Pernambuco. Sociodemographic and clinical variables and those related to alcohol and tobacco use were evaluated through interviews and telephone contact. Results: There was a twofold increase in the frequency of alcohol use of less than 1 day/week (2 vs 4) and a variation of 2 days/month (0 vs 4). In men there was an increase in the minimum and maximum dose and in women the maximum dose allowed. Approximately 50% reduced their tobacco use and 95.8% (69) of the individuals did not take at least one puff of their cigarettes. Conclusion: Individuals had their lifestyles altered, regarding the increase in the frequency of alcohol consumption and reduction in smoking when comparing before and during the pandemic period. DOI:https://doi.org/10.56238/sevened2024.018-074